2003
DOI: 10.1111/j.1744-7348.2003.tb00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the interaction between cryptochromes and phytochromes in blue light‐induced coiling and prehaustoria development of dodder (Cuscuta campestris) seedlings

Abstract: Previous studies demonstrated that blue, near far-red and a mixture of red and far-red light stimulate, while red light inhibits coiling and prehaustoria development in young excised de-etiolated dodder seedlings. In this study, evidence was obtained for the involvement of cryptochromes in the mediation of coiling and prehaustoria development in response to blue light. The results indicated that coiling and prehaustoria are affected by the addition of red or far-red light and therefore are dependent on the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…From an evolutionary perspective, this preference is understandable because the plants need to be close to the host, and light there would be partially blocked and the R:FR ratio lower. In the Haidar (2003) experiments, the effect of high light intensity (mixture of R and FR lights at 200 mM m Á2 s Á1 ) on haustorium induction was less than that of lower intensity (40 mM m Á2 s Á1 ). This indicates a greater influence of the red signal at higher light intensity.…”
Section: á1mentioning
confidence: 99%
See 1 more Smart Citation
“…From an evolutionary perspective, this preference is understandable because the plants need to be close to the host, and light there would be partially blocked and the R:FR ratio lower. In the Haidar (2003) experiments, the effect of high light intensity (mixture of R and FR lights at 200 mM m Á2 s Á1 ) on haustorium induction was less than that of lower intensity (40 mM m Á2 s Á1 ). This indicates a greater influence of the red signal at higher light intensity.…”
Section: á1mentioning
confidence: 99%
“…This suggests that haustorium induction by blue light might be triggered by phytochrome. Haidar (2003) indicated a potential role of cryptochrome as a blue light receptor by using the phytochrome inhibitor Gabaculine; this compound inhibits only the phytochrome effect. The author reported that the FR effect in induction was decreased by Gabaculine but that the blue light effect was not influenced.…”
Section: á1mentioning
confidence: 99%
“…15) Additionally, FR light (700-730 nm), but not R light (600-700 nm) can induce coiling and prehaustoria development of light-grown dodder seedling (Cuscuta campestris), which is a parasitic plant of the Convolvulaceae. 16,17) So the information obtained about evolutional alteration in the molecular mechanism for receiving red light and far-red light and subsequent signal transduction in those parasites should be valuable for further elucidation of the photoperception and phototransduction systems in green plants.…”
mentioning
confidence: 99%
“…It has been suggested that coiling and induction of prehaustoria are under the control of two classes of photoreceptors: phytochromes (photoreceptors of red/far-red light) and cryptochromes (photoreceptors of blue/ultraviolet light) (Haidar 2003). Chryptochromes interact synergistically with the Pr (red light absorbing) form of phytochrome, and antagonistically with Pfr form in mediating initiation and coiling of prehaustoria (Haidar 2003).…”
Section: Growth and Developmentmentioning
confidence: 99%
“…Chryptochromes interact synergistically with the Pr (red light absorbing) form of phytochrome, and antagonistically with Pfr form in mediating initiation and coiling of prehaustoria (Haidar 2003). Phytochrome B (Furuhashi et al 1997) or phytochrome A (Haidar et al 1998) may be involved.…”
Section: Growth and Developmentmentioning
confidence: 99%